A business worth 50 million dollars - Francesco Fornari (Freedom from Fear, 2009)
Nur is a common name, but it is just as likely that it is not his real name; he has been living for some time on the coast of Kenya near Lamu, one of the last standing examples of Islamic architecture, not far from the Somali border. He is a little over forty years old, he speaks broken English and is constantly chewing on “khat,” leaves from a plant that grows in some areas of Kenya and Ethiopia which cause a mild state of euphoria and are commonly used in Somalia. Although he was initially diffident and almost scared of my questions, he overcame his hesitation in front of a few banknotes and accepted my invitation to tell his story and his experience as a pirate.